Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

For 1) t = - 18 after the statement is executed --t is done first. so t becomes 9. u get 18 to right of +. ++t gives 10. and on left of + we have 10. RHS of -= we have 28. t is now 10.

for 2) t = 38 after the statement is executed --t is done first. so t=9. RHS =9. ++t is 10 and t become 10. RHS is now 19. t-- gives 10 value and t becomes now 9. RHS of += 29.

Write t -= (++t ) + (--t) * 2 . In this first --t will be done. t =9. E1=9. Then multiplication of E1 by 2. So E1 = 18. Then ++t will be done. So t = 10. E2 = 10. Then results E1 and E2 are added. So we get t -= 28. As t is 10 at this point, this will result in -18.

write t += (t--) + (++t) + (--t) In this first --t is done. So t is 9. yu get E1 = 9. next ++t is done. so t becomes 10. E2 = 10. Now t-- is done. so t = 9. But E3 = 10 and not 9 as post-fix operator is used. Now add E1, E2, E3 to get 29. It becomes now t += 29 As t =9 at this point of time, t will become 38.

t+=t dosnt mean t= ++t !!

t += x means that t = old value of t + value of expression x

If we dont understand the values, try a program online and see result